Posttraumatic Stress Symptoms in Swedish Obstetricians and Midwives After Severe Obstetric Events: A Cross-sectional Retrospective Survey. Issue 2 (June 2018) - Wahlberg, Å.; Andreen Sachs, M.; Johannesson, K.; Hallberg, G.; Jonsson, M.; Skoog Svanberg, A.; Högberg, U.
Abstract : ( BJOG . 2017;124(8):1264–1271) Health care professionals may experience psychological reactions such as posttraumatic stress disorder (PTSD) after encountering a severe obstetric incident. The term "second victim" has been used to refer to the distress reported by health care providers after involvement in a medical error or poor patient outcome. This can be detrimental to both the provider and their future patients. This current cross-sectional retrospective study assessed the traumatic experiences reported by obstetricians and midwives following a severe obstetric event, the risk factors for developing PTSD, and the short-term and long-term professional consequences following such severe events.